A CROSS-SECTIONAL STUDY OF STRESS AMONG UNDERGRADUATE MEDICAL STUDENTS IN A TERTIARY CARE TEACHING INSTITUTE, JHARKHAND. - Md Shadab Alam; Dr. Rajendra Kumar; Lakhan Majhee (Student's Journal of Health Research, 2023)
Background Medical students are more exposed to stressful situations due to their academic pressure, difficult learning environment, and challenging competency-based medical education design that does not provide enough time for their personal life events. So, chronic stress among medical students results in depression, substance abuse, and even suicide. This study aims to determine the prevalence of stress among undergraduate medical students of RIMS, Ranchi, Jharkhand, India. Methodology  This was a cross-sectional study conducted among 258 undergraduate medical students of RIMS, Ranchi from January 2022 to December 2022. Perceived Stress Scale-10 was used to evaluate the degree of stress among undergraduate medical students. Data obtained was analyzed using MS Excel and SSS based on SPSS and Minitab (2018).  Results A total of 258 undergraduate medical students participated in the study of which 41.4% were male and 58.52% were female. Although a moderate stress rate of 68.9% was registered in most participants, 22.48% were affected by high stress. Participants in the 4th professional MBBS are more likely to experience high stress (45.06%) as compared to students in the 2nd professional MBBS, 1st professional MBBS, and 3rd professional MBBS respectively. The difference in stress severity was statistically significant at p <0.05. Conclusion Most undergraduate medical students (68.99%) have moderate stress. Female (29.8%) are more likely to have high stress. The final professional MBBS students (44.06%) have more high stress.  Recommendation Counseling services to medical college students are strongly recommended to address the stress.